(3cfR GdeYGfi aj TQM MQR GdCeGfis - (3CHh YHO Gddg eMeO Hf CMeO Hf eMeO GdehUdj GdeYQha HTYdIs; (3GdTGWHj GdebQF GdVQjQ , CHh eMeO,J (B590 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CfRd GdbQBf Ydi SHYI CMQahHYO heG UfaJ ai GdUfGYI GdTQjaI gh GdJCdja Gdefja GdehShe HMQR GdCeGfi hhLg GdJgGfi ddTjN GdTGWHi s
(3BNQgG (B:s
(3hQRbfG TaGYJge ai jhe GdOjf hgPG BNQ eG ChQOfG ef EjVGM GdeYGfi GdMQR GdCeGfi Je GdcJGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ GdYfGhjjf hCHjGJ GdbUjOI GdeTQhMI HGdMeQI s
(3YdjgG HYV GdJedjcGJ Ydi ghGeTgG JYdjbGJ s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
Keywords: (3GdbQGAGJ hGdJLhjOs